Investigating Indonesian Pre-Service Teachers' Speaking Anxiety in EFL Classroom - Ahmad Syafi'i (STKIP PGRI SIDOARJO, 2020)
The objective of this research are to investigate pre-service teachers’ speaking anxiety in EFL classroom. The subject of this research was 40 pre-service teachers of STKIP Al Hikmah Surabaya Indonesia. The research design of this study is descriptive qualitative research. The main single instrument used in this research was questionnaire. The questionnaire used in the form of Likert scale which was adopted and developed from Horwitz. In this study, questionnaire was applied as the single instruments. In analyzing data, an interactive data analysis model proposed by Miles M.B and Huberman A.M (1984) was used. The result of the study were: (1) All pre service teachers experienced speaking anxiety in EFL classroom. (2) There are five major areas of speaking anxiety experienced by pre service teachers in EFL classroom namely fear of interaction, fear of perception of others, low self esteem and lack of confidence, language proficiency, and error correction or fear of negative corection.